Essentials of Hand Surgery - Aguilera Salgado, Alexandro (IntechOpen, 2018)
Understanding the complexity of the hand and the specific reconstructive techniques is mandatory for every hand specialist. The objective of this book is to update hand specialists on the diagnosis and treatment of some of the most common pathologies affecting the hand and to provide new insights and recent advances in this field.